Muslim diversity: Islam and local tradition in Java and Sulawesi, Indonesia - Ali, Muhammad (State Institute of Islamic Studies (STAIN) Salatiga, 2011)
Based on some historical and anthropological accounts, this article examines adynamic interplay between Islam and local tradition in Indonesia with specialreference to Java and Sulawesi. It explains how local Muslims differed in theirinterpretation and application of Islam. It looks at processes of religious changeas a world religion interacts with local forces. The âlocalizationâ of Islam was aconstant feature in the expansion of Islam beyond the Arab homeland, includingSoutheast Asia. Based on the framework of âpractical Islamâ, rather than ânormativeIslamâ, and on the framework of both accommodation and conflict betweenshariâah and adat as a whole system, rather than as separate entities, it providesa greater variety of Islamic beliefs and experiences. Comparatively, Javanesepeople have been more diverse than Sulawesi people in terms of religious spectrum;Muslims in Java have incorporated animism, Hinduism, Buddhism, andIslam into their culture system. Stories about the nine saints show how earlyIslamic preachers sought to accommodate Islam with local traditions. In Sulawesi,Dato ri Bandang and the other teachers, representing the elite aristocracy whoattempted to Islamize the kingdoms and the people alike and Syeikh Yusuf, representinga strict kind of Islam, show diversity but tends to suggest a less diversepicture, when compared to Java. Despite internal diversity in Java as well as inSulawesi, Java has remained more open and tolerant with cultural diversity,whereas Sulawesi has increasingly become more legalistic.Â Berdasarkan kajian sejarah dan antropologis, artikel ini membahas hubungandinamis antara Islam dan budaya lokal di Indonesia dengan rujukan khusus padaJawa dan Sulawesi. Artikel ini menjelaskan bagaimana orang Islam lokal berbedadalam memahami dan menerapkan Islam. Artikel ini melihat proses-prosesperubahan keagamaan ketika agama dunia bergumul dengan kekuatan-kekuatanlokal. Lokalisasi Islam adalah ciri tetap dalam penyebaran Islam melampaui tanahArab, termasuk Asia Tenggara. Berdasarkan kerangka âIslam sebagaimana yangdipraktekkanâ (âIslam praktikalâ), bukan âIslam normatifâ dan kerangka akomodasidan konflik antara syariâah dan adat sebagai sistem yang menyeluruh, bukanrealitas yang terpisah, artikel ini menawarkan kemajemukan kepercayaan danpengalaman Islam. Secara komparatif, orang-orang Jawa lebih majemuk daripadaorang-orang Sulawesi dalam hal spektrum keagamaan. Orang-orang Islam diJawa memasukkan animism, agama Hindu dan Buddha, dan Islam kedalamsistem budaya mereka. Cerita-cerita tentang wali songo menunjukkan bagaimanapenyebar-penyebar Islam awal berusaha mengakomodasi Islam dengan budayabudayalokal. Di Sulawesi, Dato ri Bandang dan guru-guru lainnya, yang mewakilikaum bangsawan yang berusaha melakukan pengislaman kerajaan-kerajaan danorang-orang, dan Syeikh Yusuf yang mewakili kaum yang lebih tegas, menunjukkankeragaman keagamaan, namun tidak semajemuk di Jawa. Meskipun adakemajemukan di Jawa dan di Sulawesi, Jawa tampaknya lebih terbuka dan tolerandengan perbedaan budaya, sedangkan Sulawesi menunjukkan kecenderunganyang legalistik. Namun demikian, keagamaan jangan dipahami bersifat statis,liner, lengkap, dan selesai.